Daytime Workers with Longer Daily Rest Periods Have Smaller Sleep Debt and Social Jetlag: A Cross-Sectional Web Survey. Issue 1 (2nd January 2021) - Ikeda, Hiroki; Kubo, Tomohide; Sasaki, Takeshi; Liu, Xinxin; Matsuo, Tomoaki; So, Rina; Matsumoto, Shun; Takahashi, Masaya
ABSTRACT: Objectives : The work interval duration between the end of one workday and the start of the following workday is referred to as the daily rest period (DRP). The present study examined whether DRP – a proxy for sleep opportunity between work shifts – is associated with indicators of sleep debt and social jetlag among daytime workers. Methods : We used a web-based survey to gather data on demographics, average DRP in the previous month, time in bed (TIB), bedtime, wake-up time, and sleep timing on workdays and non-workdays. The Japanese daytime workers (n = 3, 914) were divided into seven DRP groups (hours) as follows: <11, 11, 12, 13, 14, 15, and ≥16. Results : The two-way analyses of covariance (DRP group x day) for TIB, mid-sleep as sleep timing, bedtime, and wake-up time showed significant interactions (all p < .001). Specifically, TIB was significantly shorter, and mid-sleep and wake-up time were significantly earlier on workdays than on non-workdays, across all DRP groups (all p < .001). Additionally, the different values for TIB (sleep debt), sleep timing (social jetlag), bedtime, and wake-up time were calculated by subtracting workdays from non-workdays. The trend analysis showed that workers with longer DRP (sleep opportunity) had smaller differences in TIB, sleep timing, and wake-up time between workdays and non-workdays (all p < .001). Conclusions : Overall, daytime workers reported significant sleep debt and misalignment between work and free sleep-wake periods. However, workers with shorter DRPs (less sleep opportunity between shifts) reported significantly greater amounts of sleep debt and social jetlag than did workers with longer DRPs.